Compartimentação da paisagem da bacia hidrográfica do Cauamé-RR : uma análise da fragilidade a erosão do solo - Strücker, Débora (2020)
The concern with land use and degradation in a hydrographic basin is due to its direct and indirect impacts on water resources. The Cauamé Hydrographic Basin presents itself as an important hydrographic basin in the State of Roraima due to its multiple uses and contribution to the water supply of the city of Boa Vista. Thus, the objective was to analyze the degree of soil protection in the Cauamé hydrographic basin region from the elements that form the landscape (vegetation, soils, slope, land cover and geomorphology), with the purpose of building the fragility to erosion map from soil, which is a fundamental tool before any study in the basin. To carry out this study, office work (bibliographic and cartographic survey) and field work (visit to photograph and check land cover classes) were carried out, which, analyzed in an integrated way, resulted in the land cover map. In order to achieve the objectives of the work, an image of the OLI sensor was acquired, on board the Landsat 8 satellite, from February 2020, which served as a reference for the supervised classification using the maximum likelihood pixel to pixel classifier (MAXVER). In the training phase, the pixels corresponding to the eight classes of soil cover (urban area, humid areas, exposed soil, cultivation, plowing, riparian forest, forest and water bodies) were identified in the image. The land cover map, together with other elaborated thematic maps (soils, geomorphology, slope and vegetation), went through the AHP analysis process after being transformed into a numerical map (Fuzzy weighting), generating the erosion fragility map. Data processing was performed using Spring and ArcGis software version 10.5. With the development of the work it was possible to elaborate the map of the fragility to soil erosion of the Cauamé Basin, divided into colors, which demonstrate the fragility variations from the lowest to the highest. It was concluded that the Cauamé Basin area has areas for cultivation and land use, but for the most part it is still covered by its original vegetation. Also, the areas most fragile to erosion are the APP areas, the residual reliefs, and urban and expansion areas due to the anthropic impacts of the removal of the vegetation cover.